2001
DOI: 10.1046/j.1365-2567.2001.01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor‐α potentiates CR3‐induced respiratory burst by activating p38 MAP kinase in human neutrophils

Abstract: SUMMARYCR3 and FccRs are the main receptors involved in the phagocytic process leading to engulfment and killing of microbes by production of reactive oxygen intermediates (ROI) and degranulation. Various in¯ammatory mediators, such as tumour necrosis factor-a (TNF-a) and lipopolysaccharide (LPS), are known to prime neutrophils leading to increased bactericidal responses, but the underlying mechanism of priming has only been partially elucidated. The purpose of this study was to investigate how TNF-a primes ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 40 publications
5
34
1
Order By: Relevance
“…A similar mechanism could operate with regard to ANCA and would be consistent with a previous report that ANCA preferentially engage Fc␥RIIIb (14). However, we found that homotypic Fc␥RIIIb cross-linking led directly to Syk phosphorylation in TNF-␣-primed neutrophils, which concurs with the results of other investigators who previously primed neutrophils with a higher dose of TNF-␣ (16,35). The explanation for this phenomenon remains unknown, but it suggests that Fc␥RIIIb can mediate Syk phosphorylation independent of Fc␥RIIa and that ligation of Fc␥RIIIb by ANCA-Fc may directly induce Syk phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A similar mechanism could operate with regard to ANCA and would be consistent with a previous report that ANCA preferentially engage Fc␥RIIIb (14). However, we found that homotypic Fc␥RIIIb cross-linking led directly to Syk phosphorylation in TNF-␣-primed neutrophils, which concurs with the results of other investigators who previously primed neutrophils with a higher dose of TNF-␣ (16,35). The explanation for this phenomenon remains unknown, but it suggests that Fc␥RIIIb can mediate Syk phosphorylation independent of Fc␥RIIa and that ligation of Fc␥RIIIb by ANCA-Fc may directly induce Syk phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, it was reported that blockade of the common ␤ 2 integrin antigen CD18 completely inhibits the ANCA-induced respiratory burst (8). Mac-1 (CD11b/CD18) may cooperate with Fc␥RIIa and Fc␥RIIIb in neutrophil activation, and specific Mac-1 cross-linking directly induces a respiratory burst in a manner augmented by TNF-␣ (15,16). Another area of interest, which has thus far received little attention, is the involvement of the high-affinity Fc␥ receptor Fc␥RI (CD64) in neutrophil activation by ANCA.…”
mentioning
confidence: 99%
“…Degranulation in neutrophils and macrophages is regulated by p38 MAPK (53,54), and it was recently suggested that p38 MAPK enhances phagosomal maturation by increasing granule mobility via Rab (34). We therefore speculated that p38 MAPK could be part of the signal transduction involved in the Cdc42-regulated translocation of granules.…”
Section: Discussionmentioning
confidence: 96%
“…Besides its key contribution to the anti-Aspergillus innate response (9,14,23,39), TNF-␣ represents an essential cytokine involved in DC maturation (42). Indeed, the TNF-␣ present in the supernatants from A. fumigatus-infected DC could determine the induction of a partial maturation of DC, characterized by the acquisition of CD83 and the absence of CCR7.…”
Section: Fumigatus-matured DC and Il-12 Family Members 1485mentioning
confidence: 99%